Анна Австрийская или Мушкетеры королевы: исторический роман в трех томах (Г. Борн) - Борн Георг (1993)
Экземпляры: аб. ЦБ (2017.02.05) / Инвентарный номер: 3074 / Цена: / Сис.шифр: 84(4Гем) / Авт.знак: Б82 / ББК: 84(4Гем)